2011
DOI: 10.1007/s13580-011-0182-9
|View full text |Cite
|
Sign up to set email alerts
|

Simple, quick and nondestructive method for Brassicaceae seed viability measurement with single seed base using resazurin

Abstract: A simple, quick and nondestructive test method has been developed for determining Brassicaceae seed viability with single seed using resazurin reagent (RR) which was made by resazurin and yeast mixture. The color of the RR was changed from blue to pink or colorless when the aged seeds are soaked in the RR solution for 4 hours at 35 . Seed soaking system was developed using 96-well plate and absorbance of the RR was measured at 570 nm with a multi-plate reader. Radish (Raphanus sativus L.) seeds were artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In view of this, low concentrations of ethanol from seeds or ethanol in the RR would act as respiratory substrate for yeast and the resazurin in the RR would change color. In previous a report on 6 lots of Brassicaceae seeds tested using RR, a very high prediction accuracy (98.2%) for germination was obtained through absorbance reading and the percent of the three color fractions of RR (Min and Kang, 2011).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In view of this, low concentrations of ethanol from seeds or ethanol in the RR would act as respiratory substrate for yeast and the resazurin in the RR would change color. In previous a report on 6 lots of Brassicaceae seeds tested using RR, a very high prediction accuracy (98.2%) for germination was obtained through absorbance reading and the percent of the three color fractions of RR (Min and Kang, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…The test is based on the reduction of resazurin by the respiration activity of the bacteria contained in milk, and the quality of milk is determined according to the degree of decolorization of the solution after it has been added to milk. Min and Kang (2011) developed a technique to determine Brassicaceae seed viability using a resazurin and yeast mixture (resazurin reagent; RR). The color of the RR changed from blue to pink or colorless when the aged seeds were soaked in the solution for 4 hours at 35 , but did not change in the non-aged seeds.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 25 years, some of the applications of Raz as a bioreactive tracer have included the detection of chemical toxicity [ Liu , 1986], sludge activity in wastewater treatment [ Strotmann et al , 1993; McNicholl et al , 2007], cell viability in mammals [ O'Brien et al , 2000], abundance of contaminant‐degrading microorganisms [ Guerin et al , 2001], differentiation of aerobic and anaerobic bacteria [ Karakashev et al , 2003], detection of activity of disinfectants against biofilms [ Mariscal et al , 2009], seed viability assays [ Min and Kang , 2011] and, most recently, cell counting in breast cancer treatment experiments [ Ziegler et al , 2011]. Particularly important for applications in hydrology and biogeochemistry, these studies reported that Raz can be reduced by strict aerobes, facultative anaerobes, aerotolerant and microaerophile organisms, but not by strict anaerobes.…”
Section: Introductionmentioning
confidence: 99%
“…Field and laboratory studies have shown that the transformation of Raz in filtered water is negligible compared to that in sediments (Haggerty et al, , ). Also, studies have shown that Raz can be reduced to Rru by strict aerobes, facultative anaerobes, aerotolerant, and microaerophile organisms but not by strict anaerobes and thus preferentially indicates aerobic metabolism (Guerin et al, ; González‐Pinzon et al, , ; Karakashev et al, ; Knapp et al, ; Mariscal et al, ; McNicholl et al, ; Min & Kang, ; O'Brien et al, ; Strotmann et al, ; Ziegler et al, ). Combined, these ideal properties of the Raz‐Rru system have helped hydrologists and ecologists quantify parameters and fluxes related to exchange with, and storage within, metabolically active transient storage zones in the near subsurface (e.g., benthic, hyporheic, and riparian zones) (González‐Pinzón et al, , , ; Haggerty et al, ; Knapp et al, , ).…”
Section: Introductionmentioning
confidence: 99%